Nitrogênio e boro no cultivo de couve-flor ‘Verona CMS’ no médio norte mato-grossense - Fernandes, Solange Ossuna (2014)
Cauliflower is considered a greenery of great economic importance, especially to smallholders, to be a culture profitable in small areas. In Brazil, the main producing regions are South and Southeast. Curd size and quality are the most important aspects of your marketing, being influenced by nutrients absorbed during the crop cycle, standing out, among then, nitrogen and boron. Nitrogen (N) is the nutrient that most affects plant growth, because it is present in the composition of the most important biomolecules, such as ATP, NADH, NADPH, chlorophyll, proteins and numerous enzymes. In cauliflower, N deficiency affects the vegetative plant variables, decreasing number of leaves, plant height, stem diameter, leaf area, and dry matter. Nitrogen fertilization accelerates the development of the plant, increasing yield and cauliflower curd diameter, whereas N is responsible for fast and vigorous vegetative developing, that is associated with good development of the blossom. Boron (B) is essential for cellular growth, mainly in young plant parts like buds, apical meristems, and reproductive structures, being essential for cell wall structure and function, because stabilizes pectic network and regulates de pore size of cell wall. Boron fertilization for Brassicacea in Brazil is often recommended, whereas an existents result indicates positive response for this micronutrient utilization, which has long since had its essentiality proven, although their primary function is not clarified. Fertilizers levels currently recommended underestimate the real need of culture in different places cultivation, making it difficult to obtain high productivity and trade patterns. Therefore, the aim of this study was evaluate N and B influence in the cultivation of cauliflower ‘Verona CMS’.